Conversation and Gaze in Urban and Rural First Grade Classrooms; [Conversación y Mirada en Aulas Urbanas y Rurales de Primer Grado] - Villalta-Paucar, M (Universidad Austral de Chile, 2022)
The aim of this study was to analyze the effect of different types of regulatory exchanges and gaze of teachers on their students during real-time classroom interactions in the first year of urban and rural primary school. The study is descriptive using quantitative methodology. Twenty-nine female teachers of urban and rural schools in Chile participated. A real lesson was filmed where the teachers used eye tracking lenses. Two types of regulatory exchanges were recorded: mediated (MRE) and only regulatory exchanges (RE). The fixation time of the teachers’ gaze on students’ faces was determined. Results indicate that: (1) The average range of teacher fixation on students’ faces is significantly higher in rural classroom teachers compared to urban classroom teachers; (2) the structure of the MRE does not affect the fixation time of gaze of classroom teachers. © 2022, Estudios Pedagogicos. All Rights Reserved.